EcoFriends: Multicultural Service-Learning Communication for SDG 15 (Life on Land) - Cho, Hyunjun (Institut Komunikasi dan Bisnis LSPR, 2025)
Environmental degradation and biodiversity loss require higher education to adopt pedagogical models that connect sustainability learning with real-world practice. This study proposes the EcoFriends Multicultural Service-Learning Model as a design-based conceptual framework for operationalizing Sustainable Development Goal 15 (Life on Land) in higher education. Developed through literature synthesis, model construction, theoretical benchmarking, and replicability guidelines, EcoFriends integrates four components: knowledge integration, campus-based environmental action, community engagement, and multicultural reflection and collaboration. The model contributes by (1) explicitly aligning service-learning with biodiversity-focused SDG 15 priorities, (2) operationalizing intercultural pedagogy through structured multicultural collaboration and reflection, and (3) framing sustainability education as a communicative and civic engagement process linking students, universities, and community partners. As a conceptual contribution, EcoFriends is modular, adaptable, and resource-efficient, offering practical guidance for institutions seeking to localize SDG 15 through inclusive and practice-oriented education.